Penerapan Gaya Ekspositoris dan Observasional dalam Penyutradaraan Film Dokumenter Breaking Boundaries: Ruang yang Sama - Muhammad Fauzan Yuzril; Nurmaya Prahatmaja; Jimi Narotama Mahameruaji (Pusat Riset dan Inovasi Nasional, 2025)
The documentary film Breaking Boundaries: Ruang Yang Sama explores the experiences of athletes with disabilities in Bandung Regency as they confront prevailing social stigma. Rather than allowing their physical limitations to hinder them, these athletes turn such conditions into motivation to pursue achievements in sports. This documentary employs a directorial concept that combines expository and observational approaches. The expository method utilizes voice-over narration to present data-based information, while the observational style captures the athletes’ activities naturally, without direct intervention from the filmmaker. The filmmaking process follows three key stages: pre-production, production, and post-production. As the director, the author is responsible for guiding the visual narrative to support the intended message. The documentary applies a three-act narrative structure—introduction, conflict development, and resolution—which contributes to the coherence of the storyline. Through this combination, the film aims to portray the realities faced by disabled athletes and foster greater appreciation for their efforts and accomplishments in sports